Estátuas andarilhas : as miniaturas na imaginária missioneira : sentidos e remanescências - Ahlert, Jacqueline (2012)
Among the numerous remainders of the sculptural production of the jesuiticas doctrines of the Paraguayan Province, this study contemplates the miniatures and the medium port images. Under historical, anthropological and aesthetic perspectives of analysis, these statues present in the day-to-day of the missional villages, amalgamating the European and Indigenous contributions - , are understood as material culture of a long duration historical phenomenon, expression of the development of the religious and aesthetic autonomy of the missionary. From the second half of the century XVIII on , they constituted themselves as a reminiscence through the presence in the religious praxis of the human groups that dispersed and incorporated in the Spanish and Portuguese colonial states, compounding, afterwards, collections of the independent countries of huge area of the Southern America.